(untitled) (Revista de Ensino em Artes, Moda e Design, 2024)
This article examines the role of higher education in design in social transformation, guided by the principles of inclusion and sustainability, through the strengthening of university extension. To do so, the case study of the exhibition honoring Zuzu Angel installed at the National Shoe Museum was taken as a starting point. This exhibition was related to the extension project "Fashion and Inclusion: design and clothing for people with visual disabilities," which aims to promote the inclusion of people with visual disabilities. This project, in turn, is carried out by integrating extension activities into undergraduate curricula, specifically analyzing the Fashion course at Feevale University. The closeness that extension provides between the academic and the complex reality of the community demonstrated coherence with the proposal to train designers with the ability to adopt a perspective based on social design and inclusive approaches for social transformation. During the theoretical study, the importance of critical approaches to design and pedagogies used both for teaching and as the basis for their methodologies was emphasized. Finally, the challenges and opportunities faced by higher education, focusing on accessibility and technological innovations to promote the inclusion of people with visual disabilities, were presented.